2015
DOI: 10.1038/srep16707
|View full text |Cite
|
Sign up to set email alerts
|

Significant contribution of stacking faults to the strain hardening behavior of Cu-15%Al alloy with different grain sizes

Abstract: It is commonly accepted that twinning can induce an increase of strain-hardening rate during the tensile process of face-centered cubic (FCC) metals and alloys with low stacking fault energy (SFE). In this study, we explored the grain size effect on the strain-hardening behavior of a Cu-15 at.%Al alloy with low SFE. Instead of twinning, we detected a significant contribution of stacking faults (SFs) irrespective of the grain size even in the initial stage of tensile process. In contrast, twinning was more sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…The strain-hardening rate of the Cu-15Al alloy is slightly lower than the Cu-11Al alloy when the grain size is about 0.6 μm, as shown in Figure 3(a), and the plastic deformation is largely undertaken by SFs and DTs since only few dislocations were detected in the Cu15Al alloy. [18] When the grain size is further increased to 1.5 and 3 μm, it is found that the strain-hardening rates especially at the later tensile process are comparable between the Cu-11Al and Cu-15Al alloys, as shown in Figure 3(b) and 3(c), which may be related to the dominating deformation modes of SFs and DTs. [18,27] It is observed that the flow stress of the Cu-15Al alloy is much higher than the Cu-11Al alloy as shown in Figure 3(a)-(c), thus resulting in a lower ductility in the Cu-15Al alloy though comparable strain-hardening rate is achieved.…”
mentioning
confidence: 60%
See 4 more Smart Citations
“…The strain-hardening rate of the Cu-15Al alloy is slightly lower than the Cu-11Al alloy when the grain size is about 0.6 μm, as shown in Figure 3(a), and the plastic deformation is largely undertaken by SFs and DTs since only few dislocations were detected in the Cu15Al alloy. [18] When the grain size is further increased to 1.5 and 3 μm, it is found that the strain-hardening rates especially at the later tensile process are comparable between the Cu-11Al and Cu-15Al alloys, as shown in Figure 3(b) and 3(c), which may be related to the dominating deformation modes of SFs and DTs. [18,27] It is observed that the flow stress of the Cu-15Al alloy is much higher than the Cu-11Al alloy as shown in Figure 3(a)-(c), thus resulting in a lower ductility in the Cu-15Al alloy though comparable strain-hardening rate is achieved.…”
mentioning
confidence: 60%
“…In contrast, only few dislocations can be detected when the SFE is smaller than 8 mJ/m 2 , but SFs and DTs play important roles in the tensile deformation process. [18] These different deformation mechanisms dominated by grain size and SFE are supposed to determine the strain-hardening behavior, thus the tensile plasticity of the Cu-Al alloys.…”
mentioning
confidence: 99%
See 3 more Smart Citations